Evaluating the efficacy of denture cleansing materials in removal of tea and turmeric stains: An in vitro study - Priyanka P Makhija; Kamal Shigli; Vaibhav Awinashe (Wolters Kluwer Medknow Publications, 2016)
Context: Extrinsic staining of acrylic resin dentures could be a major esthetic problem for denture wearers. Tea, coffee, cola, turmeric, and tobacco often cause extrinsic staining of dentures. Aim: To evaluate the efficacy of various denture cleansing materials in the removal of tea and turmeric stains and to compare the efficacy of those denture cleansers with each other in the removal of tea and turmeric stains. Materials and Methods: Heat-cured acrylic resin specimens were stained using tea and turmeric solutions. The spectrophotometer was used to determine the reflectance values of the samples and to evaluate the efficacy of various denture cleansing materials in removal of tea and turmeric stains. Three denture cleansers, namely, sodium hypochlorite, Safe plus, and Clinsodent were used in the study. Water was used as a control. Statistical Analysis Used: ANOVA test and post hoc Tukey's test were used to determine the statistical difference between the groups. Result: A statistically significant difference was found (p ≤ 0.05) between the different denture cleansing materials used. Products containing sodium perborate along with trisodium phosphate had the highest stain removing capability. Conclusion: It was found that all the denture cleansing materials used in the study were effective in removing tea and turmeric stains. Products containing sodium perborate along with trisodium phosphate had a comparatively greater stain removal capability than products containing sodium perborate along with sodium bicarbonate followed by products containing sodium hypochlorite followed by water (control).